Features of Professional Training of Specialists in the field of Public Governance and Administration - Derun, Tetyana (Theory and Practice of Public Administration, 2022)
The article considers the issues of professional training of specialists in the field of public administration. The specifics of public administration are studied. It is determined that the purpose of professional training of specialists in the field of public administration is the formation and development of a new generation of specialists in public administration. The provisions of the standard of higher education in the specialty 281 «Public Administration» for the first (bachelor’s) and second (master’s) level of higher education are studied. It is established that in order to increase the efficiency and quality of professional training of specialists in the field of public administration and administration, it is expedient to orient students to choose the specialization that will best meet their expectations regarding future employment. The importance of competencies in ensuring the successful work of future specialists in the field of public administration is justified.The American experience of training specialists in the field of public administration, in particular on the formation of professional competencies, is studied. It was found that in American educational institutions, along with the main disciplines and elective courses that students choose depending on their future specialization, in-depth courses are taught in the most relevant areas (spheres) in public policy-making.The program results of training of future specialists in the field of public administration are given. It is substantiated that the experience of the school of public administration in the United States is based on the introduction of modern trends in public administration, styles of administration, creative thinking, new information technology capabilities, rethinking the requirements for professional and personal qualities of public servants.It is expedient to improve the standard of higher specialty 281 «Public Administration» in order to balance professional competencies, their consistency with the needs of public administration, as well as review educational and professional programs and curricula containing a list of disciplines that provide different competencies.